Analysis of Protein Ligand‐Receptor Binding by Photoaffinity Cross‐Linking. (2nd February 2015) - Wu, Ling; Xu, Bin
Abstract: Photoaffinity cross‐linking is a rapidly developing technology for studying biomolecular interactions, including protein ligand‐receptor binding. This technology provides detailed binding information including receptor contact sites, active conformation of receptor‐ligand complexes, global binding surfaces, and binding modes. Advancements in genetic technology have enabled non‐natural photoactive amino acid derivatives to be incorporated into designer or target proteins, providing a host of new opportunities for manufacturing protein photo‐probes while bypassing the traditional peptide or small protein limits of classical chemical synthesis. This unit provides several protocols for performing basic photoaffinity cross‐linking and related analyses for applications in ligand‐receptor binding and protein‐protein interactions. © 2015 by John Wiley & Sons, Inc.